Cholangiocarcinoma: a 10-year experience of a single tertiary centre in the multi ethnicity-Malaysia - Yusoff, A.R.; Siti, Z.M.; Muzammil, A.R.M.; Yoong, B.K.; Vijeyasingam, R. (Malaysian Medical Association, 2012)
Cholangiocarcinoma (CCA) is a rare biliary tract epithelial malignancy. We described the clinical features of CCA patients in our institution. A 10-year retrospective study of patients with cholangiocarcinoma in University Malaya Medical Centre was conducted. Clinical data and outcomes in relation to the three anatomical groups of CCA were collected and analysed. Of the 69 patients that were included 55% were male. Mean age was 61 years. Twelve (17%) had intrahepatic, 38 (55%) perihilar and 19 (28%) distal tumour. Mean age (p=0.043), median duration of symptoms (p=0.011), jaundice (p<0.001), total bilirubin level (p=0.003), INR (p=0.005) and mean tumour size (p=0.048) were significantly related to the site of tumour. Only 12 patients had curative resection with seven R0 resections. Cholangiocarcinoma is increasingly diagnosed in our population. Despite that, the diagnosis is still often late. Age, jaundice and tumour size may predict anatomical location of CCA.